Toxicity and efficacy of lenvatinib plus pembrolizumab in advanced endometrial cancer: a real-world retrospective analysis - Barbi, Mali; Lee, Chung-Shien; Rahman, Husneara; Cheng, Kit Ling; John, Veena S. (Frontiers in Oncology, 2025)
BackgroundThe treatment landscape for advanced recurrent endometrial cancer (EC) has been transformed with the introduction of lenvatinib and pembrolizumab, supported by results from the KEYNOTE-775 trial. However, the recommended 20 mg daily lenvatinib dose often results in significant toxicity, limiting its use in clinical practice.ObjectiveTo evaluate the toxicity and efficacy of reduced (≤10 mg) versus higher (>10 mg) initial doses of lenvatinib combined with pembrolizumab in patients with advanced recurrent EC.MethodsIn this retrospective cohort study, patients with EC treated with lenvatinib and pembrolizumab were stratified by initial lenvatinib dose into reduced (≤10 mg) and higher (>10 mg) groups. Study endpoints included progression-free survival (PFS), overall survival (OS) and treatment-related toxicity.ResultsOf the 92 patients included, 62% initiated lenvatinib at ≤10 mg and only 14.1% received the recommended 20 mg dose. Baseline characteristics were comparable between groups, except for age (71.2 vs. 67.5 years; p = 0.003). Grade ≥2 adverse events occurred in 74% of patients, with half experiencing treatment interruptions, and 36% discontinuations, primarily due to fatigue, diarrhea, or thromboembolic events. While unadjusted PFS and OS did not differ significantly between groups (p = 0.074 and p = 0.148, respectively), age-adjusted analysis showed significantly higher hazard of progression or death in the reduced-dose group (HR: 2.92; 95% CI: 1.32–6.44; p = 0.008).ConclusionThis is the largest real-world study to date evaluating initial lenvatinib dosing strategies in advanced EC. Our findings suggest that although reduced starting doses (≤10 mg) are commonly used to mitigate toxicity, they may compromise efficacy. These results challenge current prescribing patterns and emphasize the need for prospective studies to define optimal dosing strategies.